2020
DOI: 10.1007/s10494-020-00113-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Soot Production and Oxidation in a Lab-Scale Rich–Quench–Lean (RQL) Burner

Abstract: Swirl-stabilized, turbulent, non-premixed ethylene-air flames at atmospheric pressure with downstream radially-injected dilution air were investigated from the perspective of soot emissions. The velocity and location of the dilution air jets were systematically varied while the global equivalence ratio was kept constant at 0.3. The employed laser diagnostics included 5 kHz planar laser-induced fluorescence (PLIF) of OH, 10 Hz PAH-PLIF, and 10 Hz laser-induced incandescence (LII) imaging of soot particles. OH-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…The 11 kW burner is a turbulent, bluff body, swirl stabilized non-premixed ethylene/air burner operating at atmospheric pressure and identical to the one used in [25,26]. Ethylene is axially injected along the axis through a straight tube 4 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 11 kW burner is a turbulent, bluff body, swirl stabilized non-premixed ethylene/air burner operating at atmospheric pressure and identical to the one used in [25,26]. Ethylene is axially injected along the axis through a straight tube 4 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…For all, the total fuel and air flow rates remain constant keeping the equivalence ratio constant at 0.3, but the air flow split between the primary annular (Up,a) and the secondary dilution jets (Ud,a), and the location of these jets (Hj), is different. These parametric variations were chosen as the work of [25,26] revealed that each change in air split, and dilution air location led to a varying degree of soot particle production both in flame and at the exhaust stimulating further investigations in this paper. The Base Case is without any dilution air.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a low number of ISRs with arbitrary spacing can still be useful as a rough estimate of soot emissions and inexpensive parametric analysis. Preliminary investigations in the ethylene Cambridge Rich-Quench-Lean (RQL) combustor [10,11,21,[45][46][47] [49], which is also a target flame of the International Sooting Flame workshop.…”
Section: Resultsmentioning
confidence: 99%